2017
DOI: 10.21043/qijis.v5i1.2027
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Values in The Tradition of Samin Community at East Java

Abstract: Samin culture is one of sub-cultures in East

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 1 publication
0
9
0
1
Order By: Relevance
“…The results showed that the traditions of Muslim community in Pasaman still hold certain beliefs outside of the Islamic value. The tradition mirrors to the tradition of calling rain (dhammong) in Madura (Hefni, 2008), bathing forty times or cebor opatoh (Syukur & Qodim, 2017) in Garut and tradition of Samin community in East Java (Oktafia & Mawardi, 2017) but has some major differences comparing with begalan in Banyumas (Hidayat, 2014). The rahat practitioners have some similarities with pananyaan in Tasikmalaya (Musadad, 2016) and lawang/ kuncen in Garut (Syukur & Qodim, 2017).…”
Section: E Applying Rahat In Islamic Shariamentioning
confidence: 81%
“…The results showed that the traditions of Muslim community in Pasaman still hold certain beliefs outside of the Islamic value. The tradition mirrors to the tradition of calling rain (dhammong) in Madura (Hefni, 2008), bathing forty times or cebor opatoh (Syukur & Qodim, 2017) in Garut and tradition of Samin community in East Java (Oktafia & Mawardi, 2017) but has some major differences comparing with begalan in Banyumas (Hidayat, 2014). The rahat practitioners have some similarities with pananyaan in Tasikmalaya (Musadad, 2016) and lawang/ kuncen in Garut (Syukur & Qodim, 2017).…”
Section: E Applying Rahat In Islamic Shariamentioning
confidence: 81%
“…Furthermore, the spirit of surah al-Ma'un has strengthened individual and group ties based on feelings of the same fate and cooperation fosters an attitude of optimism and competes in working and doing good to create a balance between material and spiritual matters. Thus Islam and customs have collaborated in society in realizing collective bonds as social capital that they can implement in their daily lives (Oktafia & Mawardi, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…It also became a habit that it is difficult to influence them with other ideas (Suyami, 2007: 29). As the attitudes are considered good in the the community, they will become a habit (Oktafia & Mawardi, 2017).…”
Section: Ss/manmentioning
confidence: 99%